Limb Girdle Muscular Dystrophy (LGMD): Case Report - Kanitkar, Shubhangi A. (J Clin Diagn Res, 2015)
We report a young male of autosomal recessive limb girdle muscular dystrophy (LGMD) with positive family history presented with gradual onset proximal muscle weakness in all four limbs since eight years and thinning of shoulders, arms and thighs. Neurological examination revealed atrophy of both shoulders with wasting of both deltoids thinning of thighs and pseudo hypertrophy of both calves, hypotonia in all four limbs. Gower’s sign was positive. Winging of scapula was present. Power was 3/5 at both shoulders, 4/5 at both elbows, 5/5 at both wrists, 3/5 at both hip joints, 3/5 at both knees, 5/5 at both ankles. All deep tendon reflexes and superficial reflexes were present with plantars bilateral flexors. Electromyography (EMG) showed myopathic pattern. He had elevated creatinine phosphokinase levels and muscle biopsy findings consistent with muscular dystrophy.